Reproducibility of late gadolinium enhancement quantification techniques in ischemic and non-ischemic heart diseases (ReLate study) - Gavrysh, Jonathan; Reisdorf, Philine; Hadler, Thomas; Mayr, Thomas; Ammann, Clemens; Gröschel, Jan; Kuhnt, Johanna; von Knobelsdorff-Brenkenhoff, Florian; Muehlberg, Fabian; Schwenke, Carsten; Fenski, Maximilian; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLate gadolinium enhancement (LGE) assessed by cardiovascular magnetic resonance (CMR) is an established metric for risk stratification and therapeutic guidance. However, consensus on the optimal technique for quantifying left ventricular (LV) LGE extent remains lacking. This study aimed to identify the most reliable method for quantifying LGE in chronic myocardial infarction (CMI), hypertrophic cardiomyopathy (HCM), and inflammatory heart disease (IHD).MethodsA retrospective analysis was conducted on 285 prospectively enrolled patients (CMI: n = 98; HCM: n = 91; IHD: n = 96). LV LGE images in short-axis orientation were analyzed twice by the same reader. The most reliable LGE quantification technique was defined as the one achieving the highest intra-observer reproducibility. A two-step study design was implemented: in the pilot phase (n = 90), three quantification methods were compared: full width at half maximum (FWHM), signal threshold vs. reference mean using 2–6 standard deviations (n-SD), and manual thresholding. Techniques demonstrating the lowest variability were then applied in a validation cohort (n = 195). A mixed model for repeated measures was used to estimate mean differences. Equivalence was confirmed if the 95% confidence interval (CI) for the mean difference remained within predefined margins.ResultsIn CMI, FWHM demonstrated the highest reproducibility, with a mean difference of 0.47% (95% CI: −0.40 to 1.35). In HCM, both the 5-SD and 6-SD techniques showed the highest reproducibility, with mean differences of 0.06% (95% CI: −1.28 to 1.39) and −0.16% (95% CI: −1.50 to 1.17), respectively. In IHD, the 5-SD and 6-SD techniques achieved the highest reproducibility, with mean differences of −0.72% (95% CI: −1.54 to 0.11) and −0.71% (95% CI: −1.54 to 0.11).ConclusionThe distribution and pattern of LGE influence the reproducibility of its quantification. FWHM provided the highest intra-observer reproducibility for sharply demarcated scars, as seen in CMI. For more diffuse fibrosis patterns, such as in HCM and IHD, both the 5-SD and 6-SD techniques offered similarly reproducible performance.